1987
DOI: 10.1111/j.1365-2648.1987.tb01354.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of senior nursing students’ immediate responses to distressed patients

Abstract: The purpose of this study was to determine whether the effectiveness of senior nursing students' immediate responses to patients is influenced by type of distress presented by patients or by type of student degree programme. Forty-four ADN and 31 BSN seniors from four schools agreed to participate. Subjects viewed two videotaped simulations of 'patients' complaining of pain and two of 'patients' manifesting emotional distress. Content validity of simulations was established through nurse experts. After each ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Stimuli (for example, slides, audiotapes, videotapes or written case studies) were sometimes applied prior to the participant’s answering the questionnaire (Devellis et al . 1984, Brettell 1987, Davis & Jameton 1987, Haggerty 1987). In quasi‐experimental and experimental studies, different methods of instruction were studied to evaluate their effectiveness (see, for example, Rickelman et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimuli (for example, slides, audiotapes, videotapes or written case studies) were sometimes applied prior to the participant’s answering the questionnaire (Devellis et al . 1984, Brettell 1987, Davis & Jameton 1987, Haggerty 1987). In quasi‐experimental and experimental studies, different methods of instruction were studied to evaluate their effectiveness (see, for example, Rickelman et al .…”
Section: Resultsmentioning
confidence: 99%
“…The difficulties some students have in distinguishing a patient’s need for psychosocial intervention can result from the anxiety some students experience in interpersonal situations (Davis & Kurtz 1991). In social situations, such as meeting new patients and responding to a patient’s emotional distress, students seem to be less able to function than when performing role‐related activities or responding to a patient’s physical discomfort, for example, pain (McKinstry 1985, Haggerty 1987). Students’ empathy levels are reported to be influenced by their general competence and attentive listening skills, and they seem to have an effect on client care, when, for example, reducing a client’s anxiety (Rogers 1986, Wheeler et al .…”
Section: Resultsmentioning
confidence: 99%
“…Orlando's model has been used as a framework for studies in nursing administration (Schmieding, 1990a(Schmieding, , 1990b and nursing education. Haggerty (1987) studied nursing students' responses to distressed patients. Furthermore, discussions of the application of Orlando's conceptual model to practice (Gillis, 1976), education (Haggerty, 1985(Haggerty, , 1987, and administration (Schmieding, 1984) exist in the literature.…”
Section: Previous Use Of Orlando's Modelmentioning
confidence: 99%
“…Haggerty (1987) studied nursing students' responses to distressed patients. Furthermore, discussions of the application of Orlando's conceptual model to practice (Gillis, 1976), education (Haggerty, 1985(Haggerty, , 1987, and administration (Schmieding, 1984) exist in the literature. No literature was found that documented an attempt to use the model as a conceptual basis for a communication study specifically about empathy.…”
Section: Previous Use Of Orlando's Modelmentioning
confidence: 99%